Kompetensi Guru dalam Mengembangkan Kurikulum 2013 pada Pembelajaran Fiqih di Kelas X Madrasah Aliyah Balongrejo Sumobito Jombang.doc - Abdul Rouf; Ayu Sugiarti (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
This study aims to describe the competence of Fiqh teachers in developing K13 for class X students at Madrasah Aliyah Balongrejo Sumobito Jombang. This research uses a qualitative approach with the type of case study research. Collecting data by observation, interviews, documentation. The data analysis is descriptive data analysis using triangulation technique, with the Miles and Huberman model, namely data reduction, data display, and verification. So that it can give meaning to the data that has been collected, and from that meaning conclusions can be drawn. The results showed that 1) The implementation of curriculum development at the education unit level in Fiqh learning for class X students at Madrasah Aliyah Balongrejo Sumobito Jombang was carried out in stages, in accordance with the principles of curriculum development. 2) The competence of Fiqh teachers here is very competent in their fields, in accordance with competency standards. 3) The driving factor for curriculum development in students' Fiqh learning is the competence possessed by Fiqh teachers, adequate facilities and extra-religious activities. The inhibiting factor is the lack of lesson hours on the overall application of K13.